Change of Dietary and Lifestyle Habits during and after the COVID-19 Lockdown in Cyprus: An Analysis of Two Observational Studies - Kyprianidou, Maria; Chrysostomou, Stavri; Christophi, Costas A.; Giannakou, Konstantinos (My University, 2022)
Background: People’s dietary and lifestyle habits appeared to be influenced by restrictive measures imposed in response to the COVID-19 pandemic. This study examines the differences in dietary and lifestyle habits during and after the lockdown measures in Cyprus. Methods: Two online cross-sectional surveys were conducted, using a self-administered, anonymous questionnaire to collect information on sociodemographic and anthropometric characteristics, smoking habits, physical activity, and dietary habits. The first survey was conducted between 6 April 2020 and 20 June 2020 (during national lockdown) while the second survey was conducted between 27 October 2021 and 20 January 2022 (post-lockdown). Results: A total of 2503 individuals participated in the study. A higher consumption of fruits, vegetables, legumes/pulses, fish, and poultry was identified during lockdown compared to the period after the lockdown. Moreover, a greater daily intake of olive oil and a lower consumption of alcohol was found during the confinement period compared to the post-confinement period. During lockdown, most participants (43.0%) never or rarely used delivery services, while the largest proportion of the participants after lockdown used delivery services 1−3 times per month (37.0%) (p < 0.001). During lockdown, around 66% of the participants were physically active, compared to 55.5% after lockdown (p < 0.001). Furthermore, when compared to those with a normal BMI, more overweight and obese respondents ordered food 1−2 times per week in both periods (p < 0.001). Conclusions: Dietary and lifestyle habits of the participants were healthier throughout the lockdown period than after the end of the restrictive measures due to the COVID-19 pandemic. It is critical to encourage the Cypriot population to maintain the healthy dietary and lifestyle habits established during the lockdown in their daily lives after the confinement.
Keywords: COVID-19; Cyprus; coronavirus; diet; lifestyle habits; lockdown; nutrition; quarantine